Project Description – hermA: Automated modelling of hermeneutic processes - Gaidys, Uta; Gius, Evelyn; Jarchow, Margarete; Koch, Gertraud; Menzel, Wolfgang; Orth, Dominik; Zinsmeister, Heike (Hamburger Journal für Kulturanthropologie (HJK), 2018)
This article sketches the theoretical and methodological background of the interdisciplinary research project hermA. It assembles five disciplines form three academic institutions in Hamburg, that work collaboratively on medical research questions relating to the usage and application of annotation in hermeneutic text analysis in their specific fields. Their common research interest in hermA based to explore possibilities for the automation of annotations.